Treatment of stabilized landfill leachate by the combination of coagulation-flocculation and advanced oxidation processes / Ahmad Razali Ishak - Ahmad Razali , Ishak (2019)
The stabilized landfill leachate (SLL) is complex wastewater that containing the high concentration of bio-recalcitrant organic matter. The application of conventional biological treatment was often found to be inefficient in reducing the organic content of SLL. Improper treated SLL can emerge into the environment and cause the soil and water pollution. Therefore, it is critical to apply the efficient treatment method to treat this hazardous wastewater before releasing it into the environment. The objective of this research was to develop and investigate the hydroxyl radical ( OH) and sulfate radical based advanced oxidation process (SR-AOP) for the treatment of SLL after coagulation-flocculation pretreatment. Coagulation-flocculation is a crucial pretreatment process to improve the effectiveness of AOP. In this study, the effectiveness of three coagulants, ferric chloride (FeCl3), aluminium sulfate (Al2(SO4)3) and polyaluminum chloride (PACL), in the removal of chemical oxygen demand (COD) was evaluated. The result indicated that the removal of COD was more favorable when the coagulation-flocculation was performed in the slightly acidic condition. Among the selected coagulants, FeCl3 is the most efficient coagulant which produced 65-75% COD removal. However, it was found that the concentration of COD after pretreatment was still not complying with the maximum discharge standard of many countries indicating the requirement of further treatment. Pre-treated SLL was further treated with Fenton (Fe2+ & H2O2) and SR-AOP. In Fenton treatment, the result showed that 55% of COD was successfully reduced. However, the ecotoxicity of the Fenton reaction treated SLL was found to be higher than the pre-treated SLL due to the presence of H2O2 residue. In SR-AOP treatment, sulfate radical was generated using Fe(II) and Ultraviolet (UV) activation of persulfate (PS) and peroxymonosulfate (PMS). By using the optimized condition, more than 30 and 60% of COD concentration in the pre-treated leachate was successfully removed using Fe(II) and UV based SR-AOP, respectively. Since UV/SR-AOP showed higher efficiency in COD removal as compared to Fe(II)/SR-AOP, UV-based treatment was selected as the treatment for the development of laboratory scale continuous flow wastewater treatment system (CFWTS). In addition, PS was selected as the oxidants due to lower toxicity effluent production. In the continuous mode treatment, the COD removal was consistent with the previous UV/PS batch experiment. However, it required longer reaction time due to a higher volume of treated SLL. Since the changes of pH did not significantly affect the COD removal, the initial pH was adjusted to 11.5 for simultaneous removal of ammoniacal nitrogen (NH3N). In this study, 91% COD and 68% of NH3N were successfully removed from SLL. These findings indicated that the combination of coagulation-flocculation and SR-AOP could be an alternative method to be applied in a full-scale leachate treatment system.